GENETICALLY DETERMINED CARDIAC ARRHYTHMIAS - M. A. Shkolnikova; M. S. Kharlap; R. A. Ildarova (Российский кардиологический журнал, 2011)
Genetic factors play an important role in pathogenesis of many diseases. It has been shown that potential-dependent Na, K, and Ca channels have common characteristics in their molecular structure, which should be taken into account when assessing physiological functioning of these channels. Hereditary diseases due to channel pathology are called channelopathies, or primary electrical heart disorders (long QT interval syndrome, short QT interval syndrome, Brugada syndrome, catecholamine-dependent ventricular tachycardia, idiopathic ventricular fibrillation, Lenegre disease, hereditary Wolf-Parkinson-White syndrome, hereditary atrial fibrillation). The second leading cause of sudden cardiac death (SCD), after coronary heart disease, is secondary hereditary electrical disorders (hypertrophic cardiomyopathy, dilated cardiomyopathy, right ventricular arrhythmogenic dysplasia, isolated left ventricular non-compaction). Genetically determined cardiac arrhythmias (CA), with or without structural heart pathology, manifest in young age (with an exception of Brugada syndrome) and have specific phenotypic and genotypic characteristics. Timely diagnostics of these diseases should be based on ECG screening (ideally performed before 3 years of age) and EchoCG. In addition, examination of families with high SCD risk has an important diagnostic value. High total SCD risk in treated patients with genetically determined CA is an indication for cardioverter-defibrillator implantation. Optimal strategy of SCD prevention in patients with genetically determined CA includes baseline risk assessment and ongoing monitoring, according to the individual risk profile. This review describes clinical and molecular features of genetically determined CA, SCD risk criteria, and modern views on diagnostics and treatment of these patients.